2009
DOI: 10.1348/147608308x332401
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained chronic fatigue and core conflictual relationship themes: A study in a chronically fatigued population

Abstract: Patients' perception of interpersonal relationships as distressing may be pivotal in understanding these results. Implications for clinical intervention and future research are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Research into the interpersonal problems of CFS patients is scarce. However, previous studies suggest that interpersonal difficulties may be typical of patients with this condition (Goetz et al , 2005; Vandenbergen, Vanheule, Rosseel, Desmet, & Verhaeghe, 2008). This is also the case for patients with a chronic cardiovascular or auto‐immune disease (Lacaille, White, Backman, & Gignac, 2007), yet the cause of this relation is not clear.…”
Section: Discussionmentioning
confidence: 88%
“…Research into the interpersonal problems of CFS patients is scarce. However, previous studies suggest that interpersonal difficulties may be typical of patients with this condition (Goetz et al , 2005; Vandenbergen, Vanheule, Rosseel, Desmet, & Verhaeghe, 2008). This is also the case for patients with a chronic cardiovascular or auto‐immune disease (Lacaille, White, Backman, & Gignac, 2007), yet the cause of this relation is not clear.…”
Section: Discussionmentioning
confidence: 88%
“…Another study examining interpersonal problems reported by CFS patients during semi-structured clinical interviews revealed that fatigue was strongly related to the perception of interpersonal relations as primarily distressing, and to a disbelief in the power of social interaction in overcoming distress. More strongly fatigued CFS patients also felt more disrespected than less strongly fatigued patients [18].…”
Section: Introductionmentioning
confidence: 93%